Juridical Review of The Provision of Catering Services In Theory And Practice And Problematic at PT. Well Harvest Winning Alumina Refenery Site Kendawangan, Ketapang Regency, West Kalimantan - Limas Mentari Putri (Authentica, 2020)
Traditional Covenant Law theory has characteristics emphasizing the importance of legal certainty and predictability.  The main function of one of the contracts is to provide certainty about the binding of an agreement between the parties so that the principles of good faith in the civil law system and promissory estoppel in the common law legal system. which in this article the author will discuss PT ADEN's contractual agreement with PT Well Harvest Winning Refinery Alumina in the catering contract for employees of PT Well Harvest Winning Alumina Refinery which discusses whether the agreement made between the customer and the catering party has qualified the validity of the agreement and the issues contained in the valid agreement.Keywords: Treaty Law Theory, Civil Law, Agreement.